Dry weight targeting: The art and science of conventional hemodialysis. Issue 6 (6th June 2018) - Ohashi, Yasushi; Sakai, Ken; Hase, Hiroki; Joki, Nobuhiko
Abstract: Fluid volume overload is common and is associated with adverse outcomes in hemodialysis patients. Practicing physicians individually manage fluid volume balance in their dialysis patients according to blood pressure, interdialytic weight gain, cardiac function, nutritional status, and other comorbidities. However, accurate assessment of fluid volume status remains a concern. Indicators of dry weight target have been explored further with newer concepts and technologies. In general, total body water comprises approximately 50%‐60% of adult body weight (range, 45%‐75%), and water comprises 73.3% of lean body mass. The standard hydration status between intracellular water and extracellular water is maintained at a ratio of 62:38 in healthy adults, which, however, is influenced universally by body cell volume driven by age and muscle mass. Fluid volume imbalance in dialysis patients also is characterized primarily by decreased body cell mass associated with aging and muscle attenuation, as well as excess extracellular water content associated with sodium retention, which may be associated with the reserve capacity for volume overload. Indeed, dialysis patients with a leaner body mass have a higher prevalence of hypertension, poorer hypertension control, and greater left ventricular hypertrophy. Understanding of these body composition changes by aging and sarcopenia can aid clinical decision making in the dry weight assessments in dialysis patients. Advising patients with consistently high interdialytic weight gain to practice salt restriction and providing appropriate nutritional support for malnourished patients with downward trajectory in their dry weight would be of great help to achieve optimal fluid volume status.